Combining building performance and life cycle assessment in early design stages: Developing a tool for parametric building sustainability assessment - Magnusson, Emil (My University, 2022)
Life Cycle Assessments (LCA) and Building Performance Assessments (BPA) are today mainly introduced in the late stages of building design, although decisions with the largest influence on both building performance and environmental impact are taken already in the early design stages. Implementation of both LCA and BPA from the beginning of the design process allows for consideration of the multifaceted influence of architectural design decisions in the stages when they are the most effective. The present study aimed to identify the requirements for, and develop, a framework that integrates LCA and BPA for application early in the architectural design process. The thesis covers the requirement-based development of a parametric tool through the application of an incremental prototyping method. First, a literature and a tool review were conducted to identify and compile the barriers for the implementation of LCA and BPA in early design stages and the potential conflicts between the respective workflows. The barriers and conflicts were converted into tool requirements divided into four themes: required knowledge, design supportiveness, relevance to architects, and applicability in early design stages. The incremental prototyping method demonstrated useful potential through the parallel development of several prototypes, which allowed for isolated implementation of the requirements and a quick iterative development process for each prototype. However, further iterations are required for a more profound evaluation of the method. The resulting tool is a proof-of-concept integrating performance indicators quantifying embodied carbon, energy performance, daylight, and sunlight conditions into a common framework. Evaluated through a tool demonstration and a survey, with potential users, the tool was found to be promising for application in early stages. The evaluation showed agreement that the scope of the tool was suitable for independent use by architects to guide the design development based on several LCA and BPA indicators.
Keywords: Life cycle assessment, building performance, early design stages, sustainable building design, incremental prototyping